Considerations in Using Videoconferencing to Assess Multi-learner Classes of Layperson CPR: A Benchmark Study (International Journal of First Aid Education)
As COVID-19 pushed many activities into the virtual space, many CPR training agencies were left to consider the role that videoconferencing may play in providing learners the opportunity to complete their learning. However, this challenged program managers to consider a pivotal question: Can facilitators of first aid effectively assess skills through videoconferencing? In this study, 45 instructors were exposed to mock videoconferences of layperson CPR learners, consisting of two classes each of 1-, 4-, 9-, and 12-learners in size. Overall, study participants were able to correctly identify the specific errors made by learners – or correctly make a declaration of no error – only 38.5% of the time. When the criterion was broadened to a pass/fail decision (i.e., correctly identifying that there is an error – regardless of the specific nature of the error), performance improved to 53.8%. Although this accuracy may not be acceptable for certain learning contexts, it should not be used as the sole reason of withholding CPR education in the virtual space across-the-board. An unstructured discussion held with study participants during the study provides insight into further considerations that should be accommodated for in future work aimed at improving instructor performance in the videoconferencing space.